2022
DOI: 10.1126/sciadv.add2288
|View full text |Cite
|
Sign up to set email alerts
|

Spatially targeted brain cancer immunotherapy with closed-loop controlled focused ultrasound and immune checkpoint blockade

Abstract: Despite the challenges in treating glioblastomas (GBMs) with immune adjuvants, increasing evidence suggests that targeting the immune cells within the tumor microenvironment (TME) can lead to improved responses. Here, we present a closed-loop controlled, microbubble-enhanced focused ultrasound (MB-FUS) system and test its abilities to safely and effectively treat GBMs using immune checkpoint blockade. The proposed system can fine-tune the exposure settings to promote MB acoustic emission–dependent expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 75 publications
2
15
0
Order By: Relevance
“…UMBO was optimized to disturb one hemisphere; however, in our PK analysis, we used a whole-brain homogenization method; therefore, local concentrations of nivolumab could have been higher. Consistent with our data, a study has shown that UMBO enhanced the delivery of bevacizumab 32 ~149 KDa and anti-PD1 33 compared to non-sonicated brain in a glioma mouse model. UMBO plus 200 µg of the anti-PD-L1 biweekly treatment regimen was used to maintain the higher concentration of anti-PD-L1 within the brain parenchyma.…”
Section: Discussionsupporting
confidence: 92%
“…UMBO was optimized to disturb one hemisphere; however, in our PK analysis, we used a whole-brain homogenization method; therefore, local concentrations of nivolumab could have been higher. Consistent with our data, a study has shown that UMBO enhanced the delivery of bevacizumab 32 ~149 KDa and anti-PD1 33 compared to non-sonicated brain in a glioma mouse model. UMBO plus 200 µg of the anti-PD-L1 biweekly treatment regimen was used to maintain the higher concentration of anti-PD-L1 within the brain parenchyma.…”
Section: Discussionsupporting
confidence: 92%
“…UMBO was optimized to disturb one hemisphere; however, in our PK analysis, we used a whole-brain homogenization method; therefore, local concentrations of nivolumab could have been higher. Consistent with our data, a study has shown that UMBO enhanced the delivery of bevacizumab [ 31 ] ~149 KDa and anti-PD1 [ 32 ] compared to non-sonicated brains in a glioma mouse model. UMBO plus 200 µg of the anti-PD-L1 biweekly treatment regimen was used to maintain the higher concentration of anti-PD-L1 within the brain parenchyma.…”
Section: Discussionsupporting
confidence: 92%
“…They found that FUS did not alter the frequency of CD8 + T Cells across evaluated organs significantly, but upregulated checkpoint molecules (PD-1 and TIM-3) on these cells were detected at 1-week post-FUS, suggesting the increased activation of the T Cells. Similarly, the study of Lee et al indicated that a closed-loop controlled MB-FUS system could lead to a better penetration and distribution of the anti-PD1 antibody in the GL261 glioma mouse model ( Lee H. et al, 2022 ). Their proposed delivery system increased the interaction of proinflammatory macrophages within the PD-1-expressing TME without promoting global inflammation in non-tumor tissue.…”
Section: Fus-mediated Delivery Systems Enhance the Efficacy Of Icb Fo...mentioning
confidence: 98%
“…Advances in delivery technologies, in particular, could improve the curative potential of ICB and could also reduce ICB-related toxicities ( Kubli et al, 2021 ). Multiple delivery modes, including photons ( Cheng H. et al, 2022 ; Chen et al, 2022 ), ultrasound ( Lee H. et al, 2022 ), alternating magnetic fields ( Ge et al, 2023 ), and radiofrequencies ( Shou et al, 2022 ), can increase the accumulation of small-molecule drugs within the TME, enable more efficient and precise targeting of the specific tumor and/or immune cells, re-shape the TME and reduce off-target adverse effects ( Izci et al, 2021 ). Therefore, combining ICB with various delivery platforms has been one of the promising strategies to improve ICB for solid tumors ( Gong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%